Fall-Risk Assessment in the Elderly Using the Persian Version of Fall-Risk Screening Tool: A Population-Based Study - Tabatabaei, Hoorasa Razavi (Int J Prev Med, 2020)
BACKGROUND: Falling is a serious challenge for public health and a leading cause of morbidity and mortality among the elderly. This study conducted to evaluate the psychometric properties of the Persian version of fall risk screening tool (P-FRST). METHODS: A cross-sectional study carried out from September 2018 to March 2019 on 537 elders who referred to urban health centers in Kerman, Iran. Demographic data recorded and fall-risk assessment was performed using P-FRST and the timed up and go test (TUG). The maximum possible score is 33 for P-FRST and score ≥18 is considered as high risk. The time ≥12 s in TUG test considered as a risk for falling. Data analyzed by SPSS using t-test, analysis of variance, and linear regression. RESULTS: The mean age of participants was 67.18 ± 6.93. According to P-FRST, 22% of the elderly were high risk and 62% had a moderate risk for falling. The mean score for falling risk was significantly higher in the females, illiterates, income <10 million IRRLs, and the unemployed. CONCLUSIONS: Due to the risk of falling in the elderly, it is suggested that in the comprehensive health care for the elderly, to assess the risk of falling, especially in high-risk groups, so that preventive interventions can be made.